Offences relating to decency under Islamic law and its practice in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (The Malaysian Current Law Journal Sdn Bhd, 2014)
Islam highly emphasises on marriage as it is an effective means whereby one can lead to a virtuous life free from immorality and emotional inhibition. It is a tazir offence for a man to be alone with a woman who is neither married to him nor is related to him at the degree of mahram, in any secluded place or in a house or room under circumstances which may give rise to suspicion that they were engaged in an immoral act. Likewise, zina or illicit sexual intercourse between a man and a woman who are not married to each other, is regarded as a sinful act and hence, forbidden in Islam. Severe punishment is prescribed for committing such an act. In the same vein, exposing the attractive parts of the body, walking or talking in a seductive manner, displaying ornaments (women), wearing revealing clothes, among other are prohibited in Islam. It may be added that a male person who wears a woman’s attire and poses as a woman for immoral purposes in any public place would be deemed to have committed an offence under the Syariah criminal offences enforced in Malaysia. Again, any person who acts or behaves in an indecent manner in any public place shall be guilty of an offence both under the Penal Code and the Syariah criminal offences. As from the above, Islam places high importance to decency and the upholding of moral values because it aims at maintaining the integrity of the society as a safe place to raise children and maintain lineage. Hence, this article examines the offences relating to decency under Islamic law and with reference to its application in Malaysia.